Longitudinal shock of two elastic bars with one spherical end - An, Nguyen Thuc; To, Nguyen Dang; Son, Nguyen Hung (Vietnam Journal of Mechanics, 1993)
In this paper, authors researched a problem about longitudinal shock of two free elastic bars with one spherical end in interval 0 < t < 2l2/ a2 . Authors defined wave function in the bars, tress, strain and velocity of every section. Also authors defined the force of compression caused by shock of two bars.